2007
DOI: 10.1093/ndt/gfm043
|View full text |Cite
|
Sign up to set email alerts
|

Cannulating in haemodialysis: rope-ladder or buttonhole technique?

Abstract: Compared with the rope-ladder technique, the buttonhole method offers the advantage of an easier cannulation procedure with less bad sticks, which has a special benefit for patients with limited access cannulation sites or with a fistula which is difficult to cannulate. Prolonged compression times or re-bleeding episodes did not occur, but precautions have to be taken in order to prevent infectious complications. The buttonhole method can contribute considerably to the cannulating ease of self-cannulating pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
1
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 6 publications
5
149
1
17
Order By: Relevance
“…Of these studies, eight studies reported total infections (6,7,14,(16)(17)(18)(19)(20), five studies reported systemic infections only (21)(22)(23)(24)(25), and one study reported only local infections (8). There were four RCTs (16,17,19,20) and three observational studies comparing units with different cannulation methods (7,14,23), and the remaining eight studies were observational studies comparing before and after changes (6,8,18,21,22,24,25) (Table 3). Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these studies, eight studies reported total infections (6,7,14,(16)(17)(18)(19)(20), five studies reported systemic infections only (21)(22)(23)(24)(25), and one study reported only local infections (8). There were four RCTs (16,17,19,20) and three observational studies comparing units with different cannulation methods (7,14,23), and the remaining eight studies were observational studies comparing before and after changes (6,8,18,21,22,24,25) (Table 3). Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Most of the studies were single-center, observational studies, and all were published after 2007; the total number of patients included was greater than 1612 in the majority of the studies. The studies were conducted in the United States, Europe, Canada, and Australia; four studies were conducted in an HHD setting (8,14,(22)(23)(24)(25), seven studies were conducted in an in-center hemodialysis setting (6,7,(17)(18)(19)(20)(21), and four studies were conducted in both settings (16). Most of the studies were graded as low level of evidence (Supplemental Table 3 (Figure 3).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14][15] Currently, the introduction of daily hemodialysis and the consequent increase in the number of cannulations per week can represent an additional indication for the BH technique, although some studies have shown that a greater number of cannulations per week does not necessarily relate to a reduction in vascular access survival. 9 Aiming at assessing the usefulness and efficacy of the BH technique in daily clinical practice, a protocol for creating and cannulating AVF according to the BH technique has been introduced in our service.…”
Section: Introductionmentioning
confidence: 99%